Entrevista com Dr. D. Graham Burnett / Interview with Dr. D. Graham Burnett - Rodrigues, Deise Simões; Vareto, Polyana Valente; Torres, Rute Guimarães (Temporalidades, 2014)
Entrevista concedida em dez. 2014. Tradução: Deise Simões Rodrigues Revisão: Brian Zack